2021
DOI: 10.1097/prs.0000000000008427
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial of the Accuracy of Patient-Specific Implants versus CAD/CAM Splints in Orthognathic Surgery

Abstract: Background: The maxilla position is essential for the aesthetic and functional outcomes of orthognathic surgery. Previous studies demonstrated the advantages of patient-specific implants in orthognathic surgery. However, more data are needed to confirm the superiority of patient-specific implants over surgical splints created with computer-aided design/computer-aided manufacturing (CAD/CAM). This randomized controlled trial aimed to compare the accuracy of patient-specific implants and CAD/CAM spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…A total of 566 patients from 21 articles were included for this systematic review. Eleven articles had a prospective study design [ 13 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], of which five were randomized [ 31 , 34 , 36 , 37 , 38 ], four were clinical trials [ 31 , 34 , 36 , 38 ] and two were multi-center [ 34 , 38 ]. The study characteristics are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 566 patients from 21 articles were included for this systematic review. Eleven articles had a prospective study design [ 13 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], of which five were randomized [ 31 , 34 , 36 , 37 , 38 ], four were clinical trials [ 31 , 34 , 36 , 38 ] and two were multi-center [ 34 , 38 ]. The study characteristics are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen records evaluated the accuracy of PSI for the maxilla [ 13 , 31 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], out of which eight exclusively focused on non-segmental Le Fort I procedures [ 31 , 32 , 34 , 36 , 38 , 43 , 45 , 46 ] and two on non-segmental Le Fort I procedures in conjunction with the accuracy of PSI for mandibular osteotomies [ 13 , 39 ]. Six studies included mixed single and segmental Le Fort I osteotomies [ 33 , 37 , 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the invention of 3D printing in 1984 [ 8 ], computer-aided design (CAD) and computer-aided manufacturing (CAM) have opened up new opportunities for modern medicine to improve the surgical outcome for each individual patient [ 9 , 10 ]. Many studies have already demonstrated the higher accuracy of CAD/CAM technology for intraoperative splints in orthognathic surgery [ 11 , 12 , 13 , 14 , 15 , 16 ]. Even more, patient-specific implants (PSI) have revolutionized orthognathic surgery in recent years by allowing accurate preoperative planning and by assisting the surgeon in proper positioning [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%